Relationship between Corporate Governance and CEO Compensation among Listed Firms in Tehran Stock Exchange - Irani, Mahroo; Gerayeli, Mehdi Safari (International Journal of Economics and Financial Issues, 2017)
This study aims to investigate the relationship between corporate governance and executives' compensation. This is semi-empirical study and statistical sample of research was 95 companies listed in Tehran stock exchange from 2010 to 2014. Variables ratio of non-executive board members, dichotomy of managing director responsibility, ownership of institutional shareholders and managerial ownership were considered as independent variables. Factors influencing executives' compensation were considered and the relationship between these variables was studied using multivariate regression. Findings show that there is significant relationship between duty of managing director, ownership of institutional investors and managerial ownership. However, there was no evidence for significant relationship between ratios of non-executive board members with executives' compensation. Keywords: executives' compensation, ratio of non-executive board members, dichotomy of managing director responsibility, ownership of institutional investors, managerial ownership JEL Classifications: G34, J3